1999
DOI: 10.1002/(sici)1096-9861(19990712)409:4<567::aid-cne4>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Brain weight throughout the life span of the chimpanzee

Abstract: Studies on human postmortem material report lower brain weights in older than in younger cohorts, whereas there is no apparent change with age in the rhesus monkey. In view of these contrasting results, we examined the pattern of brain weight across the life span in the chimpanzee, one of the closest biological relatives of humans. To place the study in context of the empirical life expectancy of the chimpanzee, we first performed a survival analysis on data from 275 chimpanzees that were maintained in the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…In Europe, the average life span is 73.7 years for men and 83.8 years for women (Fernandez-Ballesteros et al, 1999). Similar differences have been described in several animal species (Smith, 1989), such as rats (Rollo et al, 2002), ungulates like the red deer (Carranza et al, 2004), marsupials like the northern quolls (Dasyurus hallucatus; Humphries and Stevens, 2001) and primates like the chimpanzee (Herndon et al, 1999). However, in most mouse strains there are no differences between genders, and the same occurs in some primates like Sumatran orangutan (Wich and et al, 2004).…”
Section: Introductionsupporting
confidence: 61%
“…In Europe, the average life span is 73.7 years for men and 83.8 years for women (Fernandez-Ballesteros et al, 1999). Similar differences have been described in several animal species (Smith, 1989), such as rats (Rollo et al, 2002), ungulates like the red deer (Carranza et al, 2004), marsupials like the northern quolls (Dasyurus hallucatus; Humphries and Stevens, 2001) and primates like the chimpanzee (Herndon et al, 1999). However, in most mouse strains there are no differences between genders, and the same occurs in some primates like Sumatran orangutan (Wich and et al, 2004).…”
Section: Introductionsupporting
confidence: 61%
“…A study that examined chimpanzee postmortem brain weights demonstrated a moderated loss of about 0.79 g/y. 116 A study based on MRI detected loss of gray and white matter volume. 50 The statistics were driven by a few very old chimps (>50 yo); however, gray matter volume decline in female chimps was still significant even when very old chimps were removed from the analysis.…”
Section: Nervous System Disordersmentioning
confidence: 99%
“…The apes were selected to provide a sample covering the adult age range of the species. In our colony, the maximum age attained by a chimpanzee was 59 years, and the mean survival of females is about 25 years (Herndon et al 1999). The apes are housed in small groups of compatible individuals and are trained to cooperate with clinical examinations and scientific study.…”
Section: Subjects and Environmentmentioning
confidence: 99%